Early angiosperm diversification: evidence from southern South America - Archangelsky, Sergio (2009)
In this report, we analyze the angiosperm fossil record (micro- and megafossil) from the central and southern basins of Argentina, southern South America, deposited between the late Barremian (128.3 Ma) to the end of the Coniacian (85.8 Ma). Based on this analysis, three major stages in the evolution of the angiosperms in the southernmost region of South America are established as follows: the late Barremian– Aptian, the latest Aptian-earliest Albian, and the middle Albian- Coniacian. The comparison between our fossil data set and those from Australia, North America, Asia and Europe suggest that the evolution and diversification of the angiosperms at mid and high latitudes in both hemispheres occurred roughly synchronously.